The effect of acute exercise on environmentally induced symptoms of dry eye. Issue 2 (29th January 2020) - Peart, Daniel J.; Walshe, Ian H.; Sweeney, Emma L.; James, Emily; Henderson, Thomas; O'Doherty, Alasdair F.; McDermott, Alison M.
Abstract: The purpose of this study was to investigate the effects of acute exercise on environmentally induced symptoms of dry eye. Twelve participants without dry eye disease volunteered to complete three experimental visits in a randomized order; (1) control condition seated for 1 h at a relative humidity (RH) of 40% (CONT), (2) dry condition seated for 1 h at a RH of 20% (DRY), and (3) exercise condition seated for 40 min followed by 20 min of cycling exercise at a RH of 20% (EXER). Tear volume, tear matrix metalloproteinase 9 (MMP‐9), perception of dry eye symptoms (frequency and severity), core temperature, and ocular surface temperature (OST) were measured at the end of each exposure. The perception of dry eye frequency and MMP‐9 concentration were significantly higher in DRY compared to CONT ( P < 0.012), with no differences in EXER compared to CONT. The results suggest that an acute bout of exercise may attenuate symptoms of environmentally induced dry eye, and warrant further research. Abstract : Exposure to a desiccating environment increased the perception of dry eye symptoms and concentration of matrix metalloproteinase 9 (MMP‐9) in tears compared to a control environment. These findings were absent when participants completed an acute bout of exercise in the desiccating environment, suggesting that exercise may attenuate symptoms.